PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA KESUSILAAN (STUDI PUTUSAN NOMOR 722/PID.SUS/2020/PN.BKS) - Namira Kinanti; Ermania Ermania Widjajanti (Reformasi Hukum Trisakti, 2022)
The sophistication of Information and Communication Technology and its various uses indicate an information society. A crime found in society is a crime of decency in ITE. The research’s problem: are the actions of perpetrators of the crime spreading immoral content using Whatsapp and Instagram are properly applying Article 45 (1) in conjunction with Article 27 (1) of ITE Law? and what is the punishment for the perpetrators that spreading immoral content on Whatsapp and Instagram? This research is a normative and descriptive analytical legal research, using secondary material, analyzed qualitatively and the conclusions drawn using deductive logic. The research’s author conclude that the actions taken by the perpetrators are in accordance with the ITE Law, namely the elements in Article 27 (1) in conjunction with Article 45 (1). However, according to the author, the Public Prosecutor’s charge can be accumulated with pornography, in the provisions of Article 4 (1) letter D of the Pornography Law. In this case there is a mixed of concursus realis criminal acts. There is a mixture of concursus realis criminal acts that apply to Article 65 of  Criminal Code as a basis for ballast crimes, the maximum criminal provisions plus one third are applied.